Inclusão de estudantes com deficiência visual nos jogos de linguagem envolvendo a matemática - Silva, Paulo Roberto de Jesus (2018)
Mathematics is fundamental in the development of any person, but there is a need for modifications in their teaching and learning, also in relation to students with visual impairment (EDV) to converge with school inclusion. It was noticed a growth in enrollment of these students, including in the Federal Institute of Education, Science and Technology of Maranhão (IFMA), a scenario that accentuates tensions and challenges, diluting our interest in investigating this issue, based on a Wittgensteinian bias. In this perspective, the following research problem emerged: how does participation of students with visual impairment in language games involving mathematics teaching take place? Our thesis is that the learning of mathematical content by EDV depends on its inclusion in language games so as not to become blind to the aspect. Only within these games does the use of specialized resources facilitate such learning. The aim of the research is to analyze how EDV participation occurs in language games involving the teaching of Mathematics. Specifically, it aims to analyze concepts wittgensteinianos that can improve the understanding about the acquisition of mathematical contents by these students; as well as to understand the life forms of words pronounced in the mathematics classes in the High School of the IFMA and its consequences in the learning of students with visual deficiency. The qualitative approach research is in line with the object of study, indispensable to situate the context in the language games in which the EDV participate, or not, through a teaching that promotes conditions of signification. We chose the case study as a method by enabling the researcher to deepen the analysis of a singular situation in its context and we used bibliographical, documentary and field research. As for bibliographical research, we elaborate a theoretical framework related to the object of study in a Wittgensteinian bias. In terms of the documentary corpus, we analyze official IFMA documents. In the empirical research, we developed research in the IFMA Technical Course through a semistructured interview with six participants, two students with visual impairment (representing 100% of the students with this deficiency in the research institution) and four mathematics teachers. Twelve classes in which an EDV and two teachers participated, at different times, were observed. We present results and discussions of the research, based on the chosen bias and the words spoken by the participants of the research, attentive to the aspects that favor or hinder the inclusion of students with visual impairment in the institutional environment, especially in the classroom. Among the results we pointed out that the practices, including pedagogic, in the institution have an ambivalence regarding the provision of opportunities for participation to students with visual impairment in language games involving mathematics. Coexisting conditions favorable and unfavorable to the making of bids in these games. As evidenced by the germination of inclusion in mathematics classes, we also observe limitations imposed on the understanding of the deeper meaning of words in a kind of blindness to the aspect. At times, we noticed that the participation of EDVs in language games depended almost exclusively on interaction with students without disabilities, which limited the learning of mathematical language. When the teacher struggled to develop alternatives, not restricting himself to the use of specialized resources, to teach, allowing the use of students' words, generated conditions of meaning in the classroom. Finally, we express that some elements are indispensable for the construction and / or strengthening of an inclusive education in mathematics. Such as the need to expand opportunities for continuing education to teachers, including questions from the language. As well as, greater emphasis on promoting dialogue in the classroom, especially among students with their teacher, because that way the student will decide and the teacher will know if there was or not learning, so that they can review their practices. We conclude that promoting the participation of visually impaired students in language games is fundamental for their learning of mathematical contents, in this context specialized pedagogical resources achieve their purpose.